2006
DOI: 10.1007/s00299-006-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Auxin and root initiation in somatic embryos of Arabidopsis

Abstract: Somatic embryos of Arabidopsis thaliana can be produced from explants of developing zygotic embryos. Cultivation of explants on maturation medium results in development of three main classes of regenerative structures: adventitious shoots, fused shoots, and complete somatic embryos. The ontogeny and anatomy of these structures was examined using serial plastic sections. Furthermore, two molecular markers were assayed to monitor transcriptional auxin responses and formation of a root meristem in this process: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 32 publications
3
52
0
Order By: Relevance
“…It is known that the combined action of auxin efflux carriers PIN1, PIN4 and PIN7 plays an essential role in auxin transport, cell division and auxin distribution during all stages of zygotic embryogenesis. [36,61,64,65] Since it is well known that auxin cell-to-cell transport is mediated by auxin influx (LAX proteins) and efflux (PIN proteins) carriers [40] and the plant hormone auxin plays an important role in every aspect of plant growth and development, including embryogenesis, [1,66] we confirmed the involvement of MtLAX3 in somatic embryo development.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…It is known that the combined action of auxin efflux carriers PIN1, PIN4 and PIN7 plays an essential role in auxin transport, cell division and auxin distribution during all stages of zygotic embryogenesis. [36,61,64,65] Since it is well known that auxin cell-to-cell transport is mediated by auxin influx (LAX proteins) and efflux (PIN proteins) carriers [40] and the plant hormone auxin plays an important role in every aspect of plant growth and development, including embryogenesis, [1,66] we confirmed the involvement of MtLAX3 in somatic embryo development.…”
Section: Resultssupporting
confidence: 52%
“…E for 12À16 h. [61] Afterwards, the immature zygotic embryos were excised from the siliques under a microscope. To induce formation of embryogenic callus tissue formation, approximately 20 immature zygotic embryos were cultured on B5 solid medium supplemented with 0.9 mg/L 2.4D, and placed in dark for 14 days.…”
Section: Direct Somatic Embryogenesis Of a Thalianamentioning
confidence: 99%
“…Bassuner, Lam, Lukowitz, and Yeung (2007) examined the histology of adventitious shoot and root formation during indirect SE from immature zygotic embryo explants. Single or fused shoots were connected to the explant by a broad tissue base, whereas somatic embryos developed from isolated cell clusters with only a weak connection to the explant.…”
Section: Arabidopsis As a Model Systemmentioning
confidence: 99%
“…In our previous studies, endogenous auxin, zeatin and ABA were at high levels in highly regenerable rice callus (Liu and Lee 1996;Huang et al 2012). Auxin might be the main factor controlling cell differentiation (Bassuner et al 2007;Petrásek and Friml 2009;Rademacher et al 2012). Our previous studies indicated that endogenous auxin levels in rice calli may play critical roles during shoot regeneration (Huang et al 2012).…”
Section: Introductionmentioning
confidence: 99%